1997
DOI: 10.1161/01.atv.17.11.3092
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Genetic Defect with LDL-Receptor Activity in Cultured Cells from Patients With a Clinical Diagnosis of Heterozygous Familial Hypercholesterolemia

Abstract: In this study we have analyzed the genetic defect in 42 patients with a diagnosis of heterozygous familial hypercholesterolemia (FH) by Southern blotting, SSCP, and sequencing of PCR-amplified fragments of genomic DNA or sequencing of RT-PCR products from mRNA in cultured cells. The apoB Arg3500Gln mutation was identified in five patients. A molecular defect in the LDL-receptor gene was confirmed in 23 patients; 16 of these mutations have not been described before. No defect in the coding region, intron:exon j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…To our knowledge, only few studies have investigated the relationship between LDLR genotype and its activity (20). Although there have been a number of studies on LDLR activity measurements in FH using DiI-LDL uptake in blood peripheral lymphocytes, some causes of defective LDLR activity, such as the K790X mutation, often appear to have been overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only few studies have investigated the relationship between LDLR genotype and its activity (20). Although there have been a number of studies on LDLR activity measurements in FH using DiI-LDL uptake in blood peripheral lymphocytes, some causes of defective LDLR activity, such as the K790X mutation, often appear to have been overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Other detection systems such as Denaturing Gradient Gel Electrophoresis (DGGE) have been used in mutation screening of the LDLR 43 ± 45 without achieving detection of mutations in all patients. The detection rate in one study using DGGE was 81% 45 although the sample size was small (n=32) and the clinical criteria were very strict, for example total cholesterol 49.5 mmol/l. This confirms the importance of the clinical diagnosis with respect to the detection rate.…”
Section: Mutation Detection Ratesmentioning
confidence: 98%
“…This discovery is not surprising, as other studies have reported that a certain proportion of putative FH subjects do not have detectable mutations at the LDL-R locus. [33][34][35] From the mutation list shown in Table II, the conclusion that emerges is that Italy is like the United Kingdom, 7,33 Germany, 36 and Japan, 37 where many mutations have produced a highly heterogeneous picture, in contrast to the situation found in other countries (like Norway, Finland, and, to some extent, Denmark), where few mutations account for a large proportion of FH patients. 38 -40 For each index case, we tried to retrieve as much family data as possible to define the geographic origin of the ancestor likely to carry the mutation identified in the index case.…”
Section: Mutation Spectrum and Clustersmentioning
confidence: 99%